Complex Interpretation of Gravity and Magnetic Fields for Oil and Gas Prognosis of Western Siberia; 75th EAGE Conference & Exhibition incorporating SPE EUROPEC 2013 - Korovin M. O. Mikhail Olegovich (Non-seismic Geophysics, 2013)
Title screen